Adaptation of a Polish version of the National Youth Tobacco Survey Questionnaire. A pilot study - Lintowska, Agnieszka; Mazur, Artur (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Introduction. In today’s world, tobacco is the most common cause of morbidity and mortality and is associated with unhealthy behavior. Poland is among the countries with high rates of smoking, and occurrence of tobacco related diseases. Tobacco use by children and adolescents is a serious public health problem because of the immediate and long-lasting harmful effects on health. A large group of current smokers begin smoking during youth. The goal of the work was to culturally and linguistically adapt, and test and pre-evaluate a Polish version of the National Youth Tobacco Survey (NYTS), which identifies and monitors trends in tobacco use among young people. Materials and methods. The test was administered by a test-retest method in 2015 with participation of 47 (25 girls and 22 boys) people aged 17–18. Respondents filled out the questionnaire twice within two weeks. The compliance percentage of individual test items and correlations between individual items in repeated measurements were evaluated. Results. More than seventy percent have reliability ratios at very high or high levels with twenty five percent at moderate levels. Conclusion. The tested Polish version of the NYTS questionnaire may be used in adolescent studies.
Keywords: validation study; smoking questionnaire; tobacco; youth; attitude